Germline Genetic IKZF1 Variation and Predisposition to Childhood Acute Lymphoblastic Leukemia - Churchman, Michelle L; Qian, Maoxiang; Te Kronnie, Geertruy; Zhang, Ranran; Yang, Wenjian; Zhang, Hui; Lana, Tobia; Tedrick, Paige; Baskin, Rebekah; Verbist, Katherine; Peters, Jennifer L; Devidas, Meenakshi; et al. (Cancer cell, 2018)
Somatic genetic alterations of IKZF1, which encodes the lymphoid transcription factor IKAROS, are common in high-risk B-progenitor acute lymphoblastic leukemia (ALL) and are associated with poor prognosis. Such alterations result in the acquisition of stem cell-like features, overexpression of adhesion molecules causing aberrant cell-cell and cell-stroma interaction, and decreased sensitivity to tyrosine kinase inhibitors. Here we report coding germline IKZF1 variation in familial childhood ALL and 0.9% of presumed sporadic B-ALL, identifying 28 unique variants in 45 children. The majority of variants adversely affected IKZF1 function and drug responsiveness of leukemic cells. These results identify IKZF1 as a leukemia predisposition gene, and emphasize the importance of germline genetic variation in the development of both familial and sporadic ALL.